Context of Science on Environmental Conservation: Comparative Study between Thai and Indonesian Novice Science Teacher Students - Nuangchalerm, Prasart; El Islami, R Ahmad Zaky (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2018)
Environmental conservation is now rapidly distributed into educational sector. Two prongs of development need to describe in science education. This study aimed to study context of science in which Thai and Indonesian novice science teacher students expresses to Baduy’s society. Seventy one of Indonesian and 95 of Thai novice science teacher students were surveyed in January-February 2018. Context of science of novice science teacher students were studied. Thai novice science teacher students had mean score higher than Indonesian novice science teacher students, but statistical testing revealed that there was no significantly differences at 0.05. The context of science Thai novice science teacher students had better than the context of science of Indonesian novice science teacher students but there is no significantly differences.